2022
DOI: 10.1021/acs.jpca.2c01438
|View full text |Cite
|
Sign up to set email alerts
|

VIBFREQ1295: A New Database for Vibrational Frequency Calculations

Abstract: High-throughput approaches for producing approximate vibrational spectral data for molecules of astrochemistry interest rely on harmonic frequency calculations using computational quantum chemistry. However, model chemistry recommendations (i.e., a level of theory and basis set pair) for these calculations are not yet available and, thus, thorough benchmarking against comprehensive benchmark databases is needed. Here, we present a new database for vibrational frequency calculations (VIBFREQ1295) storing 1295 e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 401 publications
(150 reference statements)
1
23
0
Order By: Relevance
“…Instead, we find that median errors are generally a more appropriate statistical metric to judge model chemistry performance, providing a single number description of the distribution of errors in the scaled harmonic frequencies. To further assess the distribution of errors for important model chemistries, we also use box-and-whisker plots and quantify the first, second (median error), and third quartiles.…”
Section: Computational Details and Methodologymentioning
confidence: 78%
See 3 more Smart Citations
“…Instead, we find that median errors are generally a more appropriate statistical metric to judge model chemistry performance, providing a single number description of the distribution of errors in the scaled harmonic frequencies. To further assess the distribution of errors for important model chemistries, we also use box-and-whisker plots and quantify the first, second (median error), and third quartiles.…”
Section: Computational Details and Methodologymentioning
confidence: 78%
“…Comparisons between the experimental and high-level ab initio data in VIBFREQ1295 allowed us to define and further understand the best approach to assess model chemistry performance through the use of harmonic frequency scaling factors. We found that a frequency-range-specific scaling approach, specifically dividing the frequency range into three different frequency regions (low (1,000 cm –1 ), mid (1,000–2,000 cm –1 ), and high (≥2,000 cm –1 )), each one with a corresponding scaling factor, leads to significantly improved performance compared to that of the traditional global scaling approach (corresponding to a single value to scale all frequencies in the spectrum) or a high- and low-frequency division. We also found no benefit in optimizing scaling factors for different molecular groups (e.g., halogen- and non-halogen-containing molecules) or vibrational mode types (e.g., stretches and nonstretches) .…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…43 One manuscript in this virtual special issue shows that resistively heated silicon carbide microreactors have little-to-no rovibrational cooling in the expansions, but the chemical composition of the background likely will differ from that of the molecular beam emanating directly from the reactor. 44 Finally, two spectral databases are also reported in order to provide large amounts of spectral data for many molecules 45 and rich spectral characterization of CO 2 . 46 All of these considerations for spectral analysis certainly enhance inferences that can be gleaned from these types of experiments and theoretical computations informing future astrochemical observations.…”
mentioning
confidence: 99%